Traumatic retroperitoneal neuroma at the site of prior radical nephrectomy: A case report - Sadra Sepehri; Ezra Baraban; Mohammad E. Allaf; Sunil Patel (Urology Case Reports, 2025)
We present a case of a 68-year-old male with past history of renal cell carcinoma and radical nephrectomy, who developed a traumatic retroperitoneal neuroma at the site of his prior surgery thirteen years later which initially was thought to be a cancer recurrence. We review the patient's past medical history, clinical presentation, and disease course. Finally, we provide a brief review of retroperitoneal peripheral nerve lesions and discuss current approaches to their management.